Konflikt cypryjski i jego wpływ na proces integracji Turcji z Unią Europejską - Jurkowska, Beata (Gospodarka w Praktyce i Teorii, 2011)
Cyprus dispute lasts over 35 years. Prime Minister of Turkey Recep Tayyip Erdogan announced that Ankara would not accept Cyprus as the chairman of the council of the European Union in the second half of 2012 year, if there is no earlier agreement concerning uniting of the island. Cyprus was divided in 1974 in response to a coup made by the Cypriot National Guard on the President of Cyprus Makarios III. In 1983, The Turkish Republic of Northern Cyprus declared itself independent from the Republic of Cyprus. The country was condemned by the United Nations, and is not recognized by any countries other than Turkey. Ankara, which in 2005 started accession negotiations with EU refuses to recognize Republic of Cyprus inhabited mainly by Greeks what causes the conflict between both countries and remains an obstacle to Turkish aspirations to become the member of European Union.